2015
DOI: 10.2174/1874070701509010093
|View full text |Cite
|
Sign up to set email alerts
|

Factors Governing Degradation of Phenol in Pharmaceutical Wastewater by White-rot Fungi: A Batch Study

Abstract: Phenol is a major contaminant in the industrial water effluent, including pharmaceutical wastewaters. Although several physic-chemical methods for removal of phenol exist, they are of high cost, low efficiency, and generate toxic byproducts. Thus, there is a need to develop technologies for biological removal of phenol from wastewater. In this study, the degradation of phenol in pharmaceutical wastewater by monoculture of white-rot fungi was studied. The degradation rate of total phenol in batch flasks by four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…4, it can be observed that at an initial pH of 5, a higher percentage of biodegradation was observed at different temperatures. Under the same conditions, it has been found that successful phenol biodegradation ranges between pH 5 and 6, and below or above that range, the biodegradation of phenols tends to decrease (Bernats and Juhna, 2015); likewise, a maximum cellular biomass (OD600) of 2.7 was obtained at 30°C, although no significant difference was observed with the other treatments (Fig. 4).…”
Section: Resultsmentioning
confidence: 79%
“…4, it can be observed that at an initial pH of 5, a higher percentage of biodegradation was observed at different temperatures. Under the same conditions, it has been found that successful phenol biodegradation ranges between pH 5 and 6, and below or above that range, the biodegradation of phenols tends to decrease (Bernats and Juhna, 2015); likewise, a maximum cellular biomass (OD600) of 2.7 was obtained at 30°C, although no significant difference was observed with the other treatments (Fig. 4).…”
Section: Resultsmentioning
confidence: 79%
“…Similar findings indicate that Bisphenol A (0.015%) was incubated with 1.5 U/mL of Lac 1 from Grifola frondos is capable of degrading Bisphenol A 30% without the use of a mediator in 6 hrs (46) . In just seven days, T. versicolor, a white-rot fungus, was found to be the most effective of the species, being reduced by 93% total phenol content under optimal conditions (47) . This present result is efficiently applicable to degrade phenol from industrial effluents.…”
Section: Phenol Removal By Laccase Treatmentmentioning
confidence: 99%
“…The degradation of phenol is influenced by various factors, including temperature, pH, agitation, and the physical properties of contaminants [71,83]. White-rot fungi, particularly Trametes versicolor, have been found to be effective in degrading phenol, with an optimal pH of 5-6 and temperature of 25 • C [84]. A mixed microbial culture comprising Candida tropicalis, Aspergillus fumigatus, Candida albicans, Candida haemulonis, and Streptomyces alboflavus has been found to degrade phenol, with the highest degradation occurring at an initial concentration of 1000 mg/L, a temperature of 35 • C, and a pH of 7.0 [85].…”
Section: Microorganisms That Degrade Phenolic Compounds and Bioremedi...mentioning
confidence: 99%